2002
DOI: 10.1074/jbc.m207007200
|View full text |Cite
|
Sign up to set email alerts
|

Translational Regulation of Prostaglandin Endoperoxide H Synthase-1 mRNA in Megakaryocytic MEG-01 Cells

Abstract: Prostaglandin endoperoxide H synthase-1 (PGHS-1) is an abundant enzyme in platelets, where it plays a key role in the cascade of prostanoid formation. In platelets, the primary site of PGHS-1 synthesis is in precursor megakaryocytic cells. We have previously shown that in megakaryocytic MEG-01 cells, TPA induces an increase of PGHS-1 mRNA within a few hours, whereas protein increase occurs after several days of treatment. We now report that the delayed increase in PGHS-1 protein is caused by translational regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
2
7
0
Order By: Relevance
“…Our research group had previously documented regulation at the translational step of PGHS-1 enzyme synthesis within a context of MEG-01 cell differentiation following treatment with TPA [7,8]. We noted a 2 to 3-day delay between an early rise in PGHS-1 mRNA and an increase in protein steady state levels [7,8]. Our data are in agreement with other studies, which also demonstrate a delay between mRNA transcription and increase in the levels of PGHS-1 protein [9][10][11].…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our research group had previously documented regulation at the translational step of PGHS-1 enzyme synthesis within a context of MEG-01 cell differentiation following treatment with TPA [7,8]. We noted a 2 to 3-day delay between an early rise in PGHS-1 mRNA and an increase in protein steady state levels [7,8]. Our data are in agreement with other studies, which also demonstrate a delay between mRNA transcription and increase in the levels of PGHS-1 protein [9][10][11].…”
Section: Introductionsupporting
confidence: 83%
“…Previous studies from our laboratory demonstrate that translation of PGHS-1 mRNA is delayed after induction of gene expression [8]. Furthermore, this translational regulation is influenced by the presence of both the 5'UTR and the first two exons of PGHS-1 and nucleolin protein that binds to the 5'end of PGHS-1 mRNA [14].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…At the 3Ј-untranslated region of COX-2 mRNA are multiple AUUUA elements that target mRNAs for rapid exonuclease cleavage (21,26). COX-1 mRNA lacks these 3Ј-untranslated region AUrich elements, and COX-1 mRNA is stable in megakaryocytes and vascular endothelial cells (27)(28)(29). We have recently reported that the C-terminal 19-aa of COX-2 causes the enzyme to undergo proteasomal degradation via the endoplasmic reticulum-associated degradation (ERAD) pathway (18).…”
mentioning
confidence: 99%
“…The major translational control element of COX-2, the first 60 nucleotides of the 3Ј-UTR, is highly conserved across species, is AU-rich, and contains multiple repeats of the regulatory sequence AUUUA (55)(56)(57). The sequence of the 3Ј-UTR of the COX-1 transcripts is highly divergent from that of COX-2, suggesting a distinct function in the regulation of expression at the post-transcriptional and/or translational levels (10,58). The 3Ј-UTR of the G. fruticosa COX-A is more similar to COX-2, being AU-rich (73.8%) and containing many repeats.…”
Section: Evolutionary Comparison Of Cox Protein Sequences-herementioning
confidence: 99%